GAMIFICATION IN DIGITAL MARKETING: BOOSTING CUSTOMER ENGAGEMENT AND BRAND LOYALTY - Henny Noviany; Al-Amin (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
Gamification has emerged as an innovative strategy in digital marketing, offering significant potential to increase customer engagement and build brand loyalty. The research method used is literature. The findings show that gamification, when designed and implemented appropriately, can significantly increase customer interaction, encourage deeper engagement, and strengthen the relationship between consumers and brands. However, the success of gamification relies on a deep understanding of customer motivation, careful integration with broader marketing strategies, and a balance between game elements and business value.